Haggling for Rents, Relational Contracts, and the Theory of the Firm - Oliver Gürtler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper, a formal rent-seeking theory of the firm is developed. The main idea is that integration (compared to non-integration) facilitates rent-seeking for the integrating party, but makes it harder for the integrated one. In a one-period model, this implies that the rent-seeking contest becomes more uneven and the parties rent-seek less. Here, integration is optimal. In the infinitely-repeated version of the model, it is also possible for the parties to enter a relational contract, under which each promises not to engage in rent-seeking. Such a contract must be self-enforcing, for it cannot be enforced by court. It is shown that integration makes the relational contract less easily sustainable, as, due to its cost advantage, the integrating party gains more from deviating than any party under non-integration. Hence, integration is preferred, if relational contracts are not sustainable, while, otherwise, non-integration may well be preferred. Moreover, it is shown that the model's predictions are in line with many empirical facts on the choice of ownership structures.
urn:nbn:de:bvb:19-epub-13382-0
Keywords: D23; D72; D74; L14; L22; 330; Integration; non-integration; relational contracts; rent seeking